The rise and fall of acute rheumatic fever and rheumatic heart disease: a mini review - Liang, Yunmei; Yu, Dingle; Lu, Qinghua; Zheng, Yuejie; Yang, Yonghong (Frontiers in Cardiovascular Medicine, 2023)
Introduction The incidences of acute rheumatic fever (ARF) and rheumatic heart disease (RHD), which were leading causes of death in children in the 1920s, have decreased substantially. Considering the recent resurgence of scarlet fever and increased incidence of streptococcal pharyngitis in children, an investigation of the current status of ARF and RHD may be worthwhile. Objective To summarize the prevalence trends, pathogenic factors, and prevention strategies for ARF and RHD in children. Methods A selective search of literature published between January 1920 and February 2023 was done in PubMed, using the terms “acute rheumatic fever”, “rheumatic heart disease”, “group A Streptococcus”, “pharyngitis”, “pharyngeal tonsillitis”, “scarlet fever”, “impetigo”, “obstructive sleep apnea syndrome” and “child”. Results Overcrowded homes and inadequate sanitation led to recurrent group A streptococcal infection, and the causal relationship between group A streptococcal infection and ARF/RHD was well established. Streptococcal infectious diseases, such as group A streptococcal pharyngeal tonsillitis, SF, impetigo, and obstructive sleep apnea syndrome, were associated with the occurrence of ARF and RHD. ARF and RHD were still prevalent in young people of developing countries and economically poor populations of high-income countries. Universal disease registration systems were critical to locating disease outbreaks, tracking disease transmission, and identifying high-risk populations. Four-level prevention strategies were effective in reducing the incidence and mortality of ARF and RHD. Conclusions Registry and preventive measures for ARF and RHD should be strengthened in areas of dense population; poor sanitation; resurgence of SF; and high incidence of streptococcal pharyngitis, impetigo, and obstructive sleep apnea syndrome.